Digital Chirp Rate Adaptation for Increased FMCW Interception Performance in Hough Based Transforms - Erdogan, A. Yasin; Gulum, Taylan O.; Durak-Ata, Lutfiye; Yildirim, Tulay; Pace, Phillip E. (IEEE, 2014)
Radars that can hide their emissions from threat intercept receivers and radar warning receivers are called low probability of intercept (LPI) radars and wide-band linear Frequency Modulated Continuous Waveform (FMCW) is one of the most common waveform structures they use. FMCW LPI radars use different chirp rates to vary range resolution and doppler resolution. In this work we investigate the effect of chirp rate on electronic support (ES) intercept receiver systems' performance of intercepting FMCW signals. We define ES Receiver (ESR) Digital Chirp Rate (DCR) concept, find the chirp rate interval that maximizes the interception performance and finally we propose an adaptive method for improving intercept performance of the Wigner-Hough Transform (WHT) based methods using ESR-DCR concept. The investigation is performed on different ROC curves of the WHT methods.
Keywords: Digital Chirp Rate; Wigner Distribution; LPI; FMCW; Wigner-Hough Transform; Electronic Support Receiver; Engineering